Right ventricular free-wall scar: an exceptional source of post-infarction ventricular tachycardia. A case report. Issue 2 (11th May 2019) - Tritto, Massimo; Renzullo, Elvira; Zagari, Domenico; Moretti, Paolo
Abstract: Background : In patients with coronary artery disease, ventricular tachycardia (VT) is usually related to left ventricular (LV) post-infarction scars. Case summary: A case of a 78-year-old man with post-infarction VT originating from the right ventricular (RV) free wall is described. Following recurrent episodes of VT with left bundle branch block morphology and left superior axis deviation, a patient with prior myocardial infarction was submitted to catheter ablation. Two areas of abnormal bipolar electrograms were observed at 3D electroanatomical mapping: one located at the basal aspect of the posterior and postero-septal LV, and the other one extending from the antero-lateral to the posterior mid-basal RV free wall. Ventricular late potentials (LPs) were recorded within both scars, but only pacing from those located in the RV resulted in long stimulus-to-QRS latency and optimal pace-mapping. Accordingly, this substrate was deemed the culprit of the clinical VT. Radiofrequency catheter ablation aimed at eliminating all LPs recorded from both scars was effective in preventing VT recurrences at follow-up. Discussion: A post-infarction RV free-wall scar may exceptionally be responsible of VT occurrence. Right ventricular mapping should be considered in selected cases based on 12-lead electrocardiogram VT morphology and prior RV infarct.